NOSOTROPIC MECHANISMS OF DAMAGE OF ORGANS IN DIFFERENT PERIODS OF TRAUMATIC ILLNESS - Pridruga, S.M.; Gasyuk, N.V. (World of Medicine and Biology, 2012)
In the article literary data over are brought etiologic and патогенетичеких factors of traumatic illness, in detail the analysis of experimental data is conducted concerning the mechanisms of damage of different organs’ tissues in different periods.